Synthesis, Characterization, and Study of Antibacterial Activity of Some New Formazan Dyes Derivatives, Derived from 2-Mercapto Benzoxazole. (December 2018) - Mohammed, Omar A.; Dahham, Omar S.
Abstract: This research describes the preparation of new 2-mercapto benzoxazole (1) pre-prepared was reacted with 2-Aminophenol and carbon disulfide in presence of ethanolic potassium hydroxide in a single step, Then hydrazine benzoxazole (2) was synthesized from the reaction of the compound (1) with hydrazine hydrate in presence of alcohol. And aromatic aldehydes react with compound (2) to give aryl substituted (1, 3-benzoxazole-2-yl) hydrazone (3a-f). Then formazan derivatives were prepared by a reaction hydrazon and diazonium salt different compensation for aromatic amines (4a-c, 5d-f). All compounds were confirmed by their Physical data, 1 H- NMR, 13 CNMR, and FTIR for some of them, the biological activities of these compounds have been assayed against two kinds of bacteria.